Efficacy and safety of transarterial chemoembolization plus lenvatinib combined with PD-1 inhibitors versus transarterial chemoembolization plus lenvatinib for unresectable hepatocellular carcinoma: a meta-analysis - Chen, Yue; Jia, Luyao; Li, Yu; Cui, Wenhao; Wang, Jukun; Zhang, Chao; Bian, Chunjing; Luo, Tao (Frontiers in Immunology, 2024)
Background: Locoregional treatment combined with systemic therapy is expected to play a synergistic anticancer role. We conducted this systemic meta-analysis to examine the efficacy and safety of transarterial chemoembolization (TACE) plus lenvatinib with or without programmed cell death protein-1 (PD-1) inhibitors (TLP group) compared with TACE + lenvatinib (TL group) for unresectable hepatocellular carcinoma (uHCC). Methods: From the inception date to April 2024, the data from PubMed, EMBASE, the Cochrane Library, Ovid, Web of Science, and Clinical Trials. gov were used for meta-analysis. All clinical outcomes of interest included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and adverse events (AEs). The hazard ratio (HR) and risk ratio (RR) with 95% confidence intervals (CI) were used to measure the pooled effect. Results: This study included 10 retrospective cohort studies, including 1128 patients. The OS (HR=0.51; 95% CI: 0.43-0.60, P < 0.05), PFS (HR=0.52; 95% CI: 0.45-0.61, P < 0.05), ORR (RR = 1.58; 95% CI: 1.37-1.83; P < 0.05) and DCR (RR = 1.31; 95% CI: 1.20-1.43; P < 0.05) were significantly higher in TLP group than in the TL group. The incidence of AEs was acceptable. Prognostic factor analysis identified that ECOG PS (1/0), Child-Pugh class (B/A), BCLC stage (C/B) and main portal vein invasion (yes/no) were independent prognostic factors for OS. BCLC stage (C/B) and main portal vein invasion (yes/no) were independent prognostic factors for PFS.The TLP group had better efficacy for uHCC than that of the TL group, with acceptable safety.